(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Artificial groundwater recharge is a procedure by which the groundwater store is expanded at a rate surpassing the growth rate under natural states of renewal. In certain pieces of India, due to over-misuse of groundwater, decrease in groundwater levels bringing about deficiency of supply of water, and interruption of saline water in beach front regions have been watched. In such zones, there is requirement for artificial recharge of groundwater by expanding the natural invasion of precipitation or surface-water into underground arrangements by strategies, for example, water spreading, recharge through pits, shafts, wells and whatnot The decision of a specific strategy is represented by neighborhood land, geographical and soil conditions the amount and nature of water accessible for recharge and the innovative prudent practicality and social adequacy of such plans. This paper examines different issues associated with the artificial recharge of groundwater.